Relationship between resilience and self-efficacy with professional quality of life in EMS personnel - Roohangiz Norouzinia; Abbas Ebadi; Mohammad Hosein Yarmohammadian; Saied Chian; Maryam Aghabarary (Tehran University of Medical Sciences, 2021)
Background & Aim: Pre-hospital emergency staff, as the first responder group at the scene of emergencies and disasters, should be able to cope with, and maintain their physical and mental health. The aim of this study was to investigate the relationship between resilience and self-efficacy of pre-hospital emergency staff with their professional quality of life. Methods & Materials: The present study is a cross-sectional, descriptive study that was conducted in 2019. A total of 200 pre-hospital emergency operational staff from Alborz province participated in the study using proportional and convenience sampling. Data collection tools were a demographic form and three standardized questionnaires including the emergency medical services resilience scale, the Schwartz and Jerusalem self-efficacy scale, and the Stamm professional quality of life scale. Data were analyzed through the SPSS software version 20 using descriptive statistics (mean and standard deviation) and analytical statistics (Spearman correlation, one-way ANOVA and linear regression) at the significance level of P less than 0.05. Results: The mean and standard deviation of self-efficacy (29.67±5.82), resilience (123.14±17.07), compassion satisfaction (39.81±8.09), burnout (12.06±4.76), and secondary traumatic stress (23.61±7.27). There was a significant correlation between self-efficacy and three components of professional quality of life (P<0.05). Self-efficacy was positively related to compassion satisfaction and negatively related to burnout and secondary traumatic stress. Self-efficacy and resilience were also predictors of compassion satisfaction and burnout (P<0.05). The effect of self-efficacy and resilience on compassion satisfaction was positive. The results of stepwise multiple linear regression analysis showed that five components of resilience including self-management, stress outcomes, communication challenges, maintaining peace of mind and job motivation had an effect on compassion satisfaction (P<0.05). The effect of all resilience components on compassion satisfaction was positive. Conclusion: Alborz pre-hospital emergency operational staff were at an acceptable level in terms of resilience, self-efficacy and professional quality of life.